Penerapan Penerapan Best practice pada Mata Pelajaran Matematika Materi Penyajian Data di Kelas 5 untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Mutiara Sukma Anindya; Nana Hexada Dewi Pramesthi; Nur Faridah Husnul Khotimah; Lilik Puji Rahayu; Ervina Eka Subekti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This best practice study aimed to describe the implementation of the Problem Based Learning (PBL) model in improving fifth-grade students’ learning outcomes on data presentation material at SD Supriyadi 02 Semarang. The study employed a descriptive method with a best practice approach involving 29 students of class 5B during the second semester of the 2025/2026 academic year. The implementation was conducted in three learning sessions covering data tables, pictograms, and bar charts. Learning activities were designed through the stages of problem orientation, organizing students, group investigation, presentation of results, and evaluation. Data were collected through observation, documentation, and learning outcome tests. The findings revealed that the application of PBL successfully increased students’ engagement, collaboration skills, confidence, and conceptual understanding of data presentation. The average learning outcomes showed a consistent improvement, increasing from 93.31 in the first meeting to 94.76 in the second meeting and reaching 98.55 in the third meeting. Students demonstrated better abilities in organizing, interpreting, and presenting data through various visual representations. The use of contextual problems, collaborative learning activities, worksheets, and visual media contributed significantly to the success of the learning process. Therefore, Problem Based Learning is considered an effective and innovative approach for enhancing mathematics learning outcomes and developing 21st-century skills among elementary school students.